FAMILY FIRMS, BANK RELATIONSHIPS, AND FINANCIAL CONSTRAINTS: A COMPREHENSIVE SCORE CARD. (23rd November 2018) - Karaivanov, Alexander; Saurina, Jesús; Townsend, Robert M.
Abstract: We examine the effect of financial constraints on firm investment and cash flow. We combine data from the Spanish Mercantile Registry and the Bank of Spain Credit Registry to classify firms according to whether they are family‐owned, not family‐owned, or belong to a family‐linked network of firms and according to their number of banking relations (with none, one, or several banks). Our empirical strategy is structural, based on a dynamic model solved numerically to generate the joint distribution of firm capital (size), investment, and cash flow, both in cross sections and in panel data. We consider three alternative financial settings: saving only, borrowing and lending, and moral hazard constrained state‐contingent credit. We estimate each setting via maximum likelihood and compare across these financial regimes. Based on the estimated financial regime, we show that family firms, especially those belonging to networks based on ownership, are associated with a more flexible market or contract environment and are less financially constrained than nonfamily firms. This result survives stratifications of family and nonfamily firms by bank status, region, industry, and time period. Family firms are better able to allocate funds and smooth investment across states of the world and over time, arguably done informally or using the cash flow generated at the level of the network. We also validate our structural approach by demonstrating that it performs well in traditional categories, by stratifying firms by size and age, and find that smaller and younger firms are more constrained than larger and older firms.